Assessing construction players awareness with the machinery utilization in Malaysian construction sites / Noraima Shafinaz Abidin - Abidin, Noraima Shafinaz (Faculty of Architecture, Planning and Surveying, 2014)
Safety for the workers is one of the major problems in the construction industry. This is because accidents happen without knowing time or places. Accidents not only give negative effects to the workers but family members, friends, relatives or even the government. Every year, the number of accident in construction industry increased and it really, become a major problem to the countries. With safety program that had been held by the government, it managed to decrease the number of accident occurred in the construction industry. In response to the importance of safety for workers, the objective of this research is to i identify the current statutory requirement related to machineries for construction sites, to investigate the causes of the accident occur due to machineries on construction sites, and to examine the actors’ of awareness with an accident at the construction site of high rise building. The data collected can be categorized as primary data and secondary data. This method shall be used to analyze the data obtained and therefore a conclusion and recommendation will be drawn to summarize the findings. The respondent for this dissertation is contractor on the large scales of construction project. As the finding, based on 32 response that they have been sent out in Klang Valley. Accidents really give negative effect to the workers. Also throughout this research, safety measures can be taken at early stage because prevention is better than cure. This research is very important to the workers because its asset for construction industry because without them the construction will be at the least competitive stage.